“Workers in Saskatchewan Now Have a Clear-Cut Bill of Rights”: Labour Law, Social Democracy, and the Saskatchewan Trade Union Act, 1944–1950 - Smith, Charles (Labour / Le Travail, 2024)
This paper examines the politics surrounding the construction, implementation, and administration of the Saskatchewan Trade Union Act (stua) between 1944 and 1950. The act is important because it reflects the first attempt by a social democratic government in North America to construct a system of labour law that ostensibly aligned socialist ideas with the rights of workers to form trade union freedoms. This makes the stua unique in Canadian labour and political history because the legislation demonstrated the policy priorities of the Co-operative Commonwealth Federation (ccf) and the Canadian Congress of Labour as both organizations were attempting to solidify their places in postwar Canada. This history reflects the fact that the ccf and the unions, like the left in general throughout the 1940s and 1950s, defined the working class narrowly, focusing attention on white and male breadwinners with women and racialized workers very much on the periphery. The history also demonstrates the inherent contradiction within social democratic reform politics, as the act extended numerous rights to workers to organize and collectively bargain but when those same workers pushed back against government decision-making during the province’s first public-sector strike in 1948, political tensions found many of those same social democrats acting in similar manners to their private-sector counterparts. These tensions within social democratic approaches to labour relations – so evident in the Saskatchewan experience – have become a central contradiction of the movement throughout the postwar period and continue today.